Exploring the Association between Benign Anorectal Conditions and Colorectal Cancer from the Analysis of Lower Gastrointestinal Endoscopies - Başak, Fatih; Çalışkan, Yahya Kemal; Atadağ, Yıldız Büyükdereli (Ibnosina Journal of Medicine and Biomedical Sciences, 2024)
Objective Patients experiencing hemorrhoids or fissures may overlook other gastrointestinal (GI) symptoms, assuming that they are linked solely to their existing condition. However, colon cancer, often asymptomatic, can coincide with benign pathologies detected during colonoscopy. This study investigates the prevalence of colorectal cancer (CRC) in patients undergoing lower GI endoscopy for hemorrhoids and elucidates the correlation between cancer and benign pathologies identified during colonoscopy. Highlighting its potential to reveal hidden cancers emphasizes the critical role of colonoscopy in comprehensive health care.Methods The primary objective was to thoroughly investigate the prevalence of CRC in patients who underwent lower GI endoscopy for hemorrhoids. A comprehensive analysis was conducted using a dataset spanning 7 years of lower GI endoscopy. The main focus of this investigation was to determine the incidence of cancer. Additionally, a meticulous examination of accompanying benign diagnoses was performed to provide a comprehensive evaluation.Results The study cohort, comprising 6,268 patients, revealed a noteworthy coexistence of malignancies with common conditions. The revelation was of paramount significance that the total number of malignant cases within this cohort was 440. Polyps emerged as the most frequently observed condition, constituting 55.2% (n = 243) of the cases. Diverticulosis was present in 6.6% (n: 29) of cases, while ulcerative colitis was detected in 8% (n: 2) of cases. Hemorrhoids were identified in 20.7% (n: 91) of cases. The findings indicated a substantial association between these common conditions and malignancy. Specifically, it was discovered that approximately 1 in 22 individuals with hemorrhoids, 1 in 52 individuals with fissures, and 1 in 5.7 individuals with polyps were diagnosed with malignancy.Conclusion This study highlights the pivotal role of colonoscopy in uncovering hidden cancers, especially in patients with hemorrhoids. The findings emphasize the significance of doctors and patients prioritizing colonoscopy, as it allows for early detection and intervention for potential malignancies, even in the presence of hemorrhoids.
Keywords: colonoscopy; hemorrhoids; benign pathologies; malignant pathology; clinical implications